Naming Diseases in Children by the Sidrap Bugis Ethnic - Fatmawaty; Muhammad Arsyad Rahman (Journal of Public Health and Pharmacy)
This research aims to reveal the value of naming diseases in children by the Bugis ethnic group in Sidrap Regency. The type of research is qualitative with a Rapid Ethnography approach. The selection of informants used the snowball technique. Data were collected through in-depth interviews with seven traditional birth attendants, 2 parents of toddlers, two families of toddlers, two health workers, and one traditional leader, as well as focus group discussions with five health workers. Data is analyzed using content analysis, then interpreted and presented as narratives, matrices, and schemes. Test the validity of the data using triangulation of sources and methods. The research results showed that the Bugis ethnic group in Sidrap Regency gave 18 names of diseases to children. The values associated with naming illnesses in children are Jamali, the makkatenni sanro tradition, and mappallesso. Health workers should provide outreach regarding the equivalent names of diseases by the Bugis ethnic group so that errors can be minimized in handling and treating conditions in children.